2017
DOI: 10.1103/physreva.96.042717
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear stopping power of antiprotons

Abstract: The slowing down of energetic ions in materials is determined by the nuclear and electronic stopping powers. Both of these have been studied extensively for ordinary-matter ions. For antiprotons, however, there are numerous studies of the electronic stopping power, but none of the nuclear stopping power. Here, we use quantum-chemical methods to calculate interparticle potentials between antiprotons and different atoms, and derive from these the nuclear stopping power of antiprotons in solids. The results show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 61 publications
0
19
0
Order By: Relevance
“…Nevertheless it has been predicted that the S p n contribution is larger than the value for protons and becomes an important energy-loss mechanism at E k ≤ 1 keV (Fig. 1) [28,29,[46][47][48]. Past theoretical [28][29][30][31][32][33]47] and experimental [46,49] studies of the nuclear stopping power have primarily concentrated on H, H 2 , or He gas targets.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless it has been predicted that the S p n contribution is larger than the value for protons and becomes an important energy-loss mechanism at E k ≤ 1 keV (Fig. 1) [28,29,[46][47][48]. Past theoretical [28][29][30][31][32][33]47] and experimental [46,49] studies of the nuclear stopping power have primarily concentrated on H, H 2 , or He gas targets.…”
Section: Introductionmentioning
confidence: 99%
“…Antiprotons arriving with small impact parameters relative to an atom follow complex trajectories that curve toward the nucleus with larger scattering angles θ (see Fig. 2(a)) and cross sections [48] compared to protons that are deflected in the opposite direction along approximately hyperbolic trajectories in the repulsive protonnucleus potential [28,29]. Similarly to the kinematics in elastic neutron moderation, the antiproton tends to lose the largest kinetic energy ∆E per elastic collision with a target of similar mass, such as a hydrogen atom (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are two main contributions to the stopping power phenomena: (i) electronic stopping power S e [12][13][14][15][16] which is mainly due to electronic excitations of the target electrons and (ii) nuclear stopping power S n [17][18][19][20] which is due to the elastic collision of the projectile with the target nuclei, where energy is dissipated as lattice defects or vibrations. Our discussion in this paper focuses on the first category of electronic stopping and pertains to the regime in which the phenomena occur a e-mail: correaa@llnl.gov (corresponding author) in the femtosecond time scale, with explicit simulation of electron dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…So far we concentrated on the electronic contribution. Recently, Nordlund and co-workers [45] showed that there also exists a proton-antiproton asymmetry for the nuclear stopping power S n . We therefore implemented their FIG.…”
mentioning
confidence: 99%